Changes in physiology and immune system during pregnancy and coronavirus infection: A review. (December 2020) - Chen, Miaomiao; Zeng, Jing; Liu, Xiyao; Sun, Guoqiang; Gao, Ying; Liao, Jiujiang; Yu, Jiaxiao; Luo, Xin; Qi, Hongbo
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the 3rd epidemic coronavirus after severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV). Since December 2019, the outbreak of the Coronavirus Disease 2019 (COVID-19) caused by SARS-CoV-2 has aroused great attention around the world. Pregnant women and their fetuses have been concerned as a high-risk population. We explained why pregnant women are susceptible to coronavirus in terms of their adaptive changes in physiology and immune system during pregnancy, and described the associations between maternal clinical symptoms, perinatal outcomes and coronavirus infections.